TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMBUNUHAN BERENCANA DI SIDOARJO (STUDI KASUS PUTUSAN PN SIDOARJO NOMOR 230/PID.B/2023/PN SDA) - Mohammad Fikri Alfada Wijaya; Syahrul Borman; Vieta Imelda Cornelis (Jurnal Hukum Ius Publicum, 2024)
This research discusses the elements of criminal acts and the considerations of the panel of judges in one of the cases which was a crime of murder. The author is interested in studying more deeply the application of law and the legal considerations of the panel of judges regarding the crime of murder in the case study of the Sidoarjo District Court decision Number 230/Pid.B/2023/PN Sda dated 21 June 2023, especially as there is an interesting thing about the perpetrator before committing murder with the intention of carrying a sharp sickle type weapon which can be subject to Article 340 of the Criminal Code because it meets the elements of "intentionally and with prior planning to take another person's life" but based on the judge's considerations, the perpetrator was sentenced according to Article 338 of the Criminal Code. In preparing this journal, the research method used was normative juridical legal research. The normative juridical research method is library legal research which is carried out by examining library materials or secondary data alone.